Clinical and Pharmacokinetic Evaluation of Parenteral Cefoxitin in Infants and Children - Feldman, William E. (1980)
Thirty-two infants and children ranging in age from 3 to 151 months (mean, 26 months) were treated with parenteral cefoxitin (150 mg/kg per day). Ten patients with isolates of Haemophilus influenzae (six with cellulitis, two with arthritis, and two with mastoiditis), four with Staphylococcus aureus (one with lymphadenitis, one with septicemia, and two with abscess), and three patients with Streptococcus pneumoniae (one each with cellulitis, abscess, and arthritis), were clinically and bacteriologically cured by therapy. Two additional patients with septic arthritis and facial cellulitis developed meningitis with H. influenzae type b and S. pneumoniae, respectively. Minimal inhibitory and bactericidal concentrations were ≤5 μg/ml for 15 isolates. Minimal bactericidal concentrations were >20 μg/ml for one strain of S. aureus and one of H. influenzae type b. The mean peak serum levels were 81.9 and 68.5 μg/ml 15 min after intravenous or intramuscular doses, respectively. The mean elimination half-lives were 42.4 and 40.1 min after intravenous or intramuscular doses, respectively. The mean volumes of distribution were 5,540 and 4,760 ml after intravenous and intramuscular doses, respectively. Mean plasma clearance was 242 and 257 ml/min per m(2) after intravenous and intramuscular doses, respectively. Therapy was discontinued in one patient because of neutropenia, which resolved after cefoxitin was stopped. Eosinophilia and transiently elevated liver function tests occurred in eight and six patients, respectively. These data indicate that cefoxitin may be an effective treatment for infections due to susceptible bacteria in the dosage tested, but its use may be limited because of the occurrence of meningitis during therapy in some patients.